Pemetaan Posisi Hilal Terhadap Gunung Agung Dalam Penentuan Awal Bulan Kamariah Di Lokasi Rukyat Pantai Loang Baloq Mataram - Syuhada, Nurnadiyah; Herlina; Bemi Sado, Arino (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
This study aims to determine the new moon's position towards Mount Agung in mapping at the beginning of the Lunar Month at the Loang Baloq  Beach Rukyat location. Loang Baloq Beach has been a routine location for the new moon sightings carried out by the Mataram BMKG team since 2013. However, The hilal is rarely reported to be visible at Loang Baloq Beach. The presence of Mount Agung hinders the condition of the new moon. Based on the study's results, it can be determined that the condition of Loang Baloq Beach does not meet the ideal assessment criteria. This is because the west is not clear at Azimuth 294o46'36.40". Then the west horizon of the Loang Baloq beach is blocked by the presence of Mount Agung in the Karangasem district of the island of Bali. In addition, the existence of Mount Agung causes the western horizon of the Loang Baloq coast always to be unclean or always cloudy, even though the local weather conditions are hot/sunny, Although Loang Baloq Beach does not meet the ideal criteria as a place for the sighting of the new moon. However, this location has enough potential for the sighting of the new moon compared to other locations in Mataram. Even if the new moon's position from Loang Baloq is right on Mount Agung, the new moon cannot be seen, but if it is to the left and right of Mount Agung, it is still possible to see the new moon. It is also possible to see the exact position of the new moon on Mount Agung if the height of the new moon is above Mount Agung. The mapping of the new moon position is carried out in the months of Muharram, Safar, Rabiul Awal, Rabiul Akhir, Jumadil Awal, Jumadil Akhir, Rajab, Shaban, Ramadhan, Shawwal, with the results of the appearance of the new moon being to the left of Mount Agung. In contrast, the month of Dzulqoidah, Dzulhijjah with the appearance of the new moon is right with Mount Agung. When the hilal position is right at Mount Agung, the observer shifts to another location, Tanjung Mina, North Lombok Regency.